Reflections on the Transformation in Mexico. Issue 1 (2nd January 2019) - Hanrahan, Brían; Aroch Fugellie, Paulina
Abstract : This article offers panoramic portrait of Mexican politics since the election victory of Andrés Manuel López Obrador's Morena movement in July 2018. Along its path to overwhelming success, Morena presented a vision of a historic transformation of a thoroughly corrupted Mexican state. Morena's opponents viewed its emergence with anxiety, as a radical, populist, leftist force. But the new regime has been extremely cautious, affirming existing geopolitical and security commitments and pursuing conservative macroeconomic policies. Working within these constraints, the López Obrador government has largely focused on a moral transformation of the state. The context of Morena's victory was the ongoing collapse in the Mexican state's monopoly of force and its historic complicity with criminal and paramilitary violence. The government's post-election approach has included a public reckoning with state crimes, from 1968 to Ayotzinapa. But its primary strategy has been one of ostentatious political asceticism. Rhetorically, this encompasses ideas of 'political love' and 'republican austerity'; in practical terms, it includes campaigns of public frugality and the performative vulnerability of the president himself. In closing, we analyse the proposed National Guard, arguably the centrepiece of Morena's putative state transformation, a policy condemned by some as renewed militarisation in the name of utopian republicanism.